Tick (✓) the correct answer

Question:

Tick (✓) the correct answer:

(x − 6)(x − 6) = ?

(a) (x2 − 36)

(b) (x2 + 36)

(c) (x2 − 6x + 36)

(d) (x2 − 12x + 36)

Solution:

(d) $\left(x^{2}-12 x+36\right)$

$(x-6)(x-6)$

$\Rightarrow(x-6)^{2}$  (according to the formula $\left.(a-b)^{2}=a^{2}-2 a b+b^{2}\right)$

$\Rightarrow\left(x^{2}\right)-2(x)(6)+(6)^{2}$

$\Rightarrow x^{2}-12 x+36$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now